PENEGAKAN HUKUM TERHADAP PELAKU USAHA AIR MINUM DALAM KEMASAN YANG TIDAK DILENGKAPI IJIN EDAR GUNA MENJAGA KEAMANAN PANGAN - A.A. Sagung Ngurah Indradewi (Kerta Dyatmika, 2020)
The problems described in this study is law enforcement against bottled drinking water business actors not equipped with marketing permits to maintain food security and what factors are obstacles to law enforcement against bottled drinking water business operators that are not equipped with marketing permits in order to maintain food safety. This type of research is normative legal research that is moved from the absence of legal norms or legal principles. The absence of legal norms in this study is contained in the provisions of Law No. 8 of 1999 concerning Consumer Protection which does not explicitly regulate bottled drinking water business actors that are not equipped with a marketing authorization to maintain food safety. This study uses a statutory approach and a case approach. The conclusion of this study is the law enforcement against bottled drinking water business actors that are not equipped with a marketing permit to maintain food security, namely by confiscating and destroying bottled drinking water without a distribution permit in maintaining food security based on statutory regulations namely Law Number 18 Year 2012 concerning Food, besides that, administrative sanctions are also given, namely warning letters and statements to bottled water companies that have not yet completed distribution licenses. Inhibiting factors in law enforcement against bottled drinking water business actors that are not equipped with marketing permits to maintain food safety are bottled drinking water companies that are unwilling to be inspected, implementation of supervision conducted by the Central Agency for Drug and Food Supervision, lack of supervisory personnel from the Food and Drug Supervisor, consumers do not understand the rights and obligations as consumers and retailers or retailers of bottled drinking water products are less responsible for their obligations. Keywords : Business actors in bottled drinking water, consumer protection, distribution permit.